Fatigue properties and fatigue strength prediction of 439 ferritic stainless steel. (March 2023) - Men, Fei; Zhang, Mengxiao
Highlights: The compositions of and the tensile properties  of the three 439 stainless steels are similar. But the fatigue strength at room temperature is quite different. Their crack propagation resistance has negative correlation with fatigue strength. The fracture surface of high stressed samples with low fatigue life is close to that of tensile fracture. The fatigue strength of materials can be quantitatively predicted by the area of cleavage zone. The weakening of ferrite grain boundary is an important reason for the decrease of fatigue strength after the further increase of temperature. Abstract: As one of the important steel, 439 stainless steel has been widely used in automobile, construction and other fields, but the studies of its high cycle fatigue properties are not enough. In this paper, the tensile and high cycle fatigue properties of three 439 stainless steels coming from different suppliers were compared. The tensile and high cycle fatigue at room temperature, 150 °C, 350 °C and 550 °C were evaluated. The results show that the tensile properties of the studied steels are very close to each other, but their fatigue properties are different, and the fatigue strength is inversely related to the crack resistance. With the increase of temperature, carbide precipitation and solute atom diffusion affect the linear trend of fatigue strength decline of ferritic stainless steel. The weakening of ferrite grain boundary is an important reason for the decline of fatigue strength in high temperature. Based on the cleavage surface in the fatigue crack source, the fatigue strength can be predicted quantitatively.